HUBUNGAN ANTARA PEMBINAAN DAN PENGAWASAN SEKOLAH SERTA PENGETAHUAN DAN SIKAP PENGELOLA KANTIN DENGAN SANITASI KANTIN SEKOLAH DASAR NEGERI DI KOTA BINJAI TAHUN 2013 - Siti Haritsah; surya dharma; nurmaini * (Lingkungan dan Kesehatan Kerja, 2014)
Canteen is a place that can provide the food and sell it to the primary school’s children. Cleanliness and good food processing should be done in the school’s canteen to prevent food-borne disease. Canteen should have guidance and supervision from school throught Usaha Kesehatan Sekolah (UKS) program. In addition, the food handler also should understand and implement sanitation to minimize the contamination. The study’s aim to analyze the relationship among guidance, supervision of school, knowledge, attitude of food handler and sanitation of canteen in primary schools in Binjai. This study is analytic survey with cross-sectional design. Samples in this study are 56 schools that consisting of headmasters or teachers, food handlers and condition of canteens. The result of this study was the poor guidance (53.6%), poor control (55.4%), good knowledge of food handlers (53.6%), good attitude of food handlers  (58, 9%) and 57.1% of canteens were not qualifying. Beside that there was a real relationship between guidance, supervision of school and sanitation of canteen and there was a real relationship between knowledge, attitude of food handler and sanitation of canteen. Based on this study, the schools are recommended to supervise canteen and do  good guidance like counseling to the food handlers so that they can increase their knowledge to keep the cleanliness of canteens and can prepare and serve food well and healthy to students. Key Words : Guidance, supervision, knowledge, attitude, Sanitation.